The Circulation and Reading of Chivalric Books in the Peruvian Viceroyalty: Two Questions to Be Resolved - Guibovich Pérez, Pedro M. (2020)
Chivalry books were one of the most widespread literary genres in the Spanish Empire during the Sixteenth and early Seventeenth centuries. Although it has been written that they circulated and read in the Peruvian viceroyalty, the documentary evidence in this regard is insufficient. In this note, I problematize both aspects from the existing bibliography and documentary sources.